Resultados dos investimentos em ciência da tecnologia nos estados brasileiros : uma análise dos indicadores no período 2000-2012 - Brito, Leidiane Bispo (2015)
Indicators of Science, Technology and Innovation are widely used in policy documents and studies. These are essential tools to understand and monitor the processes of production, dissemination and use of research results, technologies and innovations. In this scenario the present study aims to contribute performing an empirical analysis of technological and scientific development indicators in Brazil in order to verify that investments in S & T and fact faculty numbers influence the number of international publications and investments in R & D influence the number of deposit of patents. We used the panel data methodology, aggregated information for the states. The data comprise the years 2000 to 2012, and were obtained from the Ministry of Science, Technology and Innovation ( MCTI ) , National Council for Scientific and Technological Development ( CNPq ) and the Brazilian Institute of Geography and Statistics (IBGE ) , Geocapes - System Georeferenced Information Capes Scopus and ISI Web of for the period 2000 to 2012. The basic hypothesis that investments in S & T and faculty numbers influence the number of international publications and investments in R & D influence the patent deposit number were confirmed . It was noted that investments in S & T and faculty numbers have positive impact on the number of publications which also happens with investments in R & D and patent applications meaning that these investments has resulted in scientific and technological development . It is still striking mismatch between scientific and technological development. For, in addition, the data segmented by state shows that the disparities between these is still wide. Thus it is understood that the efforts of S , T & I either through investment in human resources , either through promotion has achieved scientific and technological results, however there is still a long way to go especially with regard to the understanding of impact of these results in promoting economic and social development.